STUDY OF CHARACTERISTIC PHOTOVOLTAIC AND IMPEDANCE DYE SENSITIZED SOLAR CELL (DSSC) WITH GEL ELECTROLYTE - PUJIARTI (NIM : 20211306), HERLIN
We have successfully fabricated and characterized dye-sensitized solar cell (DSSC) using gel polymer electrolyte. Since the prototype of a dye-sensitized solar cell (DSSC) was reported in 1991 by M. GrÃƒÂ¤tzel, it has aroused intense interest both in scientific and practical viewpoints. DSSC is attractive because of some advantages, such as low cost, simple preparation procedure, and environment-friendly. The majority of the work in the recent years has been focused on the improvement of the cell performance. Mostly investigated DSSCs are built using ionic liquid electrolyte, which are prone to electrolyte leakage and low stability. Recently, DSSC with gel electrolyte have been also much studied as a promising solution to that leakage problem. We will present the fabrication of DSSC using gel electrolyte from ionic liquid in hybrid composite polymers composed of Siloxane and ethylene glycol. The structure of DSSC is consist of: conductive substrate FTO; TiO2 layer as material semiconductors; ruthenium dye; gel electrolyte. The gel electrolyte properties was characterized by electrochemical method. The DSSC characteristics using that gel electrolyte were investigated by J-V and small ac impedance measurements, which are correlated with the concentration of ionic liquid electrolyte. The experimental data show that the reduction in Jsc is not mainly due to the increase in resistance (impedance) of the electrolyte medium, however it is more related to the decrease in redox reactions as the iodide concentration decreases